Maternal Hyperglycemia Directly and Rapidly Induces Cardiac Septal Overgrowth in Fetal Rats - Erin E. Gordon; Benjamin E. Reinking; Shanming Hu; Jianrong Yao; Kok L. Kua; Areej K. Younes; Chunlin Wang; Jeffrey L. Segar; Andrew W. Norris (Journal of Diabetes Research)
Cardiac septal overgrowth complicates 10–40% of births from diabetic mothers, but perplexingly hyperglycemia markers during pregnancy are not reliably predictive. We thus tested whether fetal exposure to hyperglycemia is sufficient to induce fetal cardiac septal overgrowth even in the absence of systemic maternal diabetes. To isolate the effects of hyperglycemia, we infused glucose into the blood supply of the left but not right uterine horn in nondiabetic pregnant rats starting on gestational day 19. After 24 h infusion, right-sided fetuses and dams remained euglycemic while left-sided fetuses were moderately hyperglycemic. Echocardiograms in utero demonstrated a thickened cardiac septum among left-sided (glucose-exposed, 0.592 ± 0.016 mm) compared to right-sided (control, 0.482 ± 0.016 mm) fetuses. Myocardial proliferation was increased 1.5 ± 0.2-fold among left-sided compared to right-sided fetuses. Transcriptional markers of glucose-derived anabolism were not different between sides. However, left-sided fetuses exhibited higher serum insulin and greater JNK phosphorylation compared to controls. These results show that hyperglycemic exposure is sufficient to rapidly induce septal overgrowth even in the absence of the myriad other factors of maternal diabetes. This suggests that even transient spikes in glucose may incite cardiac overgrowth, perhaps explaining the poor clinical correlation of septal hypertrophy with chronic hyperglycemia.